2017
DOI: 10.1007/s11999-016-5138-z
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Occult Fractures of the Acetabulum Occur Frequently During Primary THA

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 29 publications
(34 reference statements)
2
66
0
2
Order By: Relevance
“…This was in contrast to men, where there was only a trend of increased risk of revision due to periprosthetic fracture after 75 years of age, and only early postoperatively. The use of uncemented components in patients with deteriorating bone stock should probably be avoided, since impaction of components may result in fissures due to fragile cortical bone (Piarulli et al 2013, Sidler-Maier and Waddell 2015, Abdel et al 2016, Hasegawa et al 2017, Dammerer et al 2019. The poorer results after uncemented stems in elderly patients are supported by literature on both THA and hemiarthroplasty (Gjertsen et al 2012, Wangen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in contrast to men, where there was only a trend of increased risk of revision due to periprosthetic fracture after 75 years of age, and only early postoperatively. The use of uncemented components in patients with deteriorating bone stock should probably be avoided, since impaction of components may result in fissures due to fragile cortical bone (Piarulli et al 2013, Sidler-Maier and Waddell 2015, Abdel et al 2016, Hasegawa et al 2017, Dammerer et al 2019. The poorer results after uncemented stems in elderly patients are supported by literature on both THA and hemiarthroplasty (Gjertsen et al 2012, Wangen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of periprosthetic fractures after uncemented THA could therefore have been even more pronounced if other designs of cemented stems were used to a larger degree (Thien et al 2014). Also on the acetabular side, uncemented components have been associated with periprosthetic fracture (Hasegawa et al 2017, Dammerer et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Major mistakes as femoral anterior notching in total knee replacement have been proven to be associated in 10-46% of cases with supracondylar fractures (17) even though some recent studies disproved that (3). Several studies reported higher rates of fractures after cementless implants and press-fit techniques (4,5,(18)(19)(20). A review carried out by Abdel et al point out that the femoral intra-operative fractures occur 14 times more often when a cementless stem is used for THA.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…Furthermore, rTHA provides information for adequate depth and position during component impaction. Hasegawa et al reported that 8.4% of cases experienced periprosthetic occult fractures of the acetabulum in primary THA, which might be ignored during surgery [25]. rTHA might reduce the rate of such occult fractures during impaction, which warrants investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%